Psychological collectivism in youth athletes on individual sport teams - Donkers, J. L.; Martin, L. J.; Evan, M. B. (International Journal of Sport and Exercise Psychology, 2018)
The purpose of the current study was to determine whether psychological collectivism could predict enjoyment and intentions to return in athletes on individual sport teams. In addition, structural interdependence and age were used as moderator variables for the proposed relationships. A total of 142 youth (Mage = 14.44 years; SD = 1.63; 62% female) completed questionnaires at two data-collection periods (T1 - psychological collectivism, structural interdependence, and age; T2 - enjoyment and intentions to return), and the results indicated that psychological collectivism positively predicted both enjoyment and intentions to return. Also, task interdependence significantly moderated the relationship between psychological collectivism and enjoyment (b = .14, t(137) = -1.90, p = .06) and intentions to return (b = -.17, t(137) = -2.07, p < .05). Specifically, in situations where athletes were required to work together during competition (e.g. relays), athletes` collectivistic orientation had a stronger relationship with both enjoyment and intentions to return. Similarly, among older athletes, collectivism had a stronger positive relationship with intentions to return (b = .05, t(138) = 2.04, p < .05). These results are discussed in terms of their theoretical and practical implications.